Kajian tentang Pengelompokan Komunikasi dalam Organisasi - Sunata, Ivan (Institut Agama Islam Negeri Kerinci, 2022)
The aimed of this study was to explore the estimations of experts in the field of communication, focusing on grouping communication in organizations. The results of the study exposed that communication consist of two kinds; oral and written communication, verbal and non-verbal communication, formal and non-formal communication, upward, downward and sideways communication. Oral communication is directly communication done by the people, while written communication focuses on writing as a medium of communication. Verbal communication is less different with verbal communication; it emphasizes the sound (voice), while non-verbal communication is done by using symbols. Formal communication is communication that follows the organizational structure, while informal communication is a type of communication that is socially approved, and its orientation is not on the organization, but rather on the individual. Downward communication shows the flow of information from superiors or superiors to subordinates to state goals improve attitudes, form opinions and others. Upward communication is communication or messages conveyed from subordinates to leaders, while lateral communication is communication that flows between functions within an organization, needed for coordination and integration of different organizational functions.